2013
DOI: 10.1016/j.jped.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency Oscillatory Ventilation in Children: A 10-year Experience

Abstract: HFOV enabled an improvement in hypercapnia and oxygenation. It is a safe option for the treatment of ARDS and severe small airway diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…As regards oxygenation improvement, we found that HFO significantly improved oxygenation after 24 hours of enrollment, a finding that is comparable with results in several pediatric studies 35,[45][46][47] and adult studies 34,36 . Also survivors among HFO group showed significant higher OI decrease percent, PaO 2 /FiO 2 after 24 hours and higher PaO 2 /FiO 2 increase percent.…”
Section: Volume 59 • Number 2 Hfo Versus CMV In Pediatric Ardssupporting
confidence: 90%
“…As regards oxygenation improvement, we found that HFO significantly improved oxygenation after 24 hours of enrollment, a finding that is comparable with results in several pediatric studies 35,[45][46][47] and adult studies 34,36 . Also survivors among HFO group showed significant higher OI decrease percent, PaO 2 /FiO 2 after 24 hours and higher PaO 2 /FiO 2 increase percent.…”
Section: Volume 59 • Number 2 Hfo Versus CMV In Pediatric Ardssupporting
confidence: 90%
“…Evidence for the use of HFOV remains weak in paediatric acute respiratory distress syndrome (PARDS). Majority of studies conducted thus far are small [10][11][12][13][14][15][16][17]. Similar to studies performed in other populations, paediatric studies of HFOV showed a benefit in short-term oxygenation without any improvement in clinical outcomes [12,18,19].…”
Section: Introductionmentioning
confidence: 60%
“…Majority of studies conducted thus far are small [10][11][12][13][14][15][16][17]. Similar to studies performed in other populations, paediatric studies of HFOV showed a benefit in short-term oxygenation without any improvement in clinical outcomes [12,18,19]. HFOV use in children with acute respiratory failure was associated with increased mortality, duration of MV and paediatric intensive care unit (PICU) stay compared to those who were not supported with HFOV [20,21].…”
Section: Introductionmentioning
confidence: 76%
“…Given the predisposition to hypoventilation and the risk of acute pulmonary edema, the mechanical ventilation of patients intoxicated with salicylates requires a lot of attention [18,19]. Highfrequency ventilation and ECMO should be considered to treat some severe intoxications, but there are limited reports on their use in pediatric toxicology [4,20].…”
Section: The Poisoning Effects On Specific Organ Systems 41 Acute Rementioning
confidence: 99%